2008
DOI: 10.1002/mus.21090
|View full text |Cite
|
Sign up to set email alerts
|

Motor unit properties of biceps brachii in chronic stroke patients assessed with high‐density surface EMG

Abstract: Abstract-Motor unit (MU) properties of the biceps brachii andFugl-Meyer score were assessed in stroke patients and healthy controls during passive and active elbow flexion and extension contractions. The level of motor recovery as assessed with the Fugl-Meyer score was correlated with the ratio of the size of the motor unit action potentials (MUAPs) at the affected side and the unaffected side. This ratio may reflect the extent to which reinnervation has occurred on the affected side. The RMS value of the MUAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 45 publications
2
42
0
Order By: Relevance
“…Nevertheless, in that study, as in our own, the group mean values of MUPs amplitude and duration did not differ significantly between hemiparetic and unaffected side. Mixed findings were reported by Kallenberg and Hermens (2009) who examined motor units characteristics of the biceps brachii muscle in 15 chronic stroke patients using high-density surface EMG method. Their analysis showed in 7 patients the MUPs were larger and in 5 smaller on the affected side as opposed to the healthy side.…”
Section: Discussionmentioning
confidence: 77%
“…Nevertheless, in that study, as in our own, the group mean values of MUPs amplitude and duration did not differ significantly between hemiparetic and unaffected side. Mixed findings were reported by Kallenberg and Hermens (2009) who examined motor units characteristics of the biceps brachii muscle in 15 chronic stroke patients using high-density surface EMG method. Their analysis showed in 7 patients the MUPs were larger and in 5 smaller on the affected side as opposed to the healthy side.…”
Section: Discussionmentioning
confidence: 77%
“…Using incremental nerve stimulations, motor unit number estimation (MUNE) techniques that rely on laborious estimation of single motor unit size have been applied to assess loss of functional motor units in paretic muscles, as a result of spinal motoneuron degeneration after stroke [18]–[20]. With advances in both surface EMG recording and processing techniques, high-density surface electrodes have also found applications in revealing hemiparetic muscle changes at both the global muscle and motor unit levels [21]. However, most of the previous methods tend to be laborious, require expensive equipment, or require patients to tolerate needles.…”
Section: Introductionmentioning
confidence: 99%
“…28 Training with a higher frequency or longer duration stimulates functional recovery of the arm. 16,17,[29][30][31] In regard to functional exercises, several studies have shown that functional training, focusing on activities of daily life that are relevant to the patient (i.e., task-specificity), results in a normalization of brain activity. 22,32 Such normalization of brain activity is related to improvements in motor control and functional abilities.…”
Section: Stroke Rehabilitationmentioning
confidence: 99%
“…These publications included several consecutive clinical trials and summaries of those clinical trials and often used the same subjects. 9,[28][29][30][31][32][33] Of these 11 studies, only the most representative summary of the clinical trials was included in our analysis 32 along with four separate articles that were clearly dissimilar in research question or experimental setup from the studies in the summary. [34][35][36][37] Three studies that used the MIME also met the selection criteria.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation